Spaces and bodies: The legacy of Italian cinema in contemporary Chinese film-making. Issue 1 (1st March 2014) - Pollacchi, Elena
Italian neorealist films have had a strong impact on Chinese cinema since the founding of the PRC in 1949. Chinese directors of the 1980s and 1990s have looked at the works of Italian neorealist directors with renewed interest and Jia Zhangke's early films have come to epitomize the lasting imprint of Italian Neorealism in China. This article investigates the influence of Italian neorealist tradition (and beyond) on Chinese film-makers whose careers started after the turn of the century and whose works share a concern for the interplay of individuals and their surroundings. The essay also argues that space has a hermeneutic role for understanding the influence of Neorealism on certain recent Chinese narrative and documentary films. In line with the perception of an increasingly fragmented society, the impact of Italian directors on contemporary Chinese film-makers such as Liu Shu, Li Ruijun and Wang Bing emerges as an on-going process of re-appropriation rather than the lasting imprint of master teaching. While textual or stylistic references may not always be immediately apparent, the influence of Italian directors on contemporary Chinese film-making becomes clearer after some close analyses of certain Chinese films in conjunction with an examination of the directors' own observations.